2021
DOI: 10.1177/2158244020988684
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Teachers’ Union Contracts on School District Efficiency: Longitudinal Evidence From California

Abstract: While the effect of teachers’ unions on school districts continues to be debated, the research literature provides few definitive conclusions to guide these discussions. In this article, we examine the relationship between teachers’ union contracts and school district efficiency. We define efficiency as the ratio of short-run productivity (student performance on standardized exams) to expenditures. We estimate a series of school district fixed effect models using measures of district collective bargaining agre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…In their recent meta-analysis of 19 studies with 77 estimates of union wage effects, Merkle and Phillips (2018) find that teachers’ unions produced an average wage impact estimated around 2–4.5% and observe that the union effects are confounded by the measures of union status, either at the individual or district level, and legal frameworks for labor-management relations. Marianno, Bruno and Strunk (2021) find that CB restrictiveness is positively associated with expenditure on students and educators.…”
Section: Literaturementioning
confidence: 75%
“…In their recent meta-analysis of 19 studies with 77 estimates of union wage effects, Merkle and Phillips (2018) find that teachers’ unions produced an average wage impact estimated around 2–4.5% and observe that the union effects are confounded by the measures of union status, either at the individual or district level, and legal frameworks for labor-management relations. Marianno, Bruno and Strunk (2021) find that CB restrictiveness is positively associated with expenditure on students and educators.…”
Section: Literaturementioning
confidence: 75%
“…When members from the teachers' union have a seat at the bargaining table, they have a voice in policies that affect working requirements for their teacher membership, and thus the opportunity to proactively shape a school district's policy agenda. Because CBAs dictate almost all aspects related to teachers' responsibilities including professional development requirements, required work hours and breaks, classroom assignments, and evaluations, unions policy influence can be quite expansive (Ballou, 2000;Goldschmidt & Stuart, 1986;Marianno et al, 2021;Moe, 2009;Strunk & Reardon, 2010). Once negotiated, CBAs go before the school board for final ratification.…”
Section: Teachers' Unions and The First And Second Faces Of Powermentioning
confidence: 99%
“…First, teachers’ unions negotiate CBAs with school district administrators. Forty-four states permit collective bargaining, and these contract negotiations provide a venue for teachers’ unions to exert considerable influence on a variety of local education policy decisions (Marianno et al, 2021; Moe, 2009; Strunk & Grissom, 2010). CBAs can cover a broad range of issues from the allocation of district funds to the basic day-to-day duties of teachers (Ballou, 2000; Strunk et al, 2018).…”
Section: Previous Literature On Teachers’ Unions’ Political Influencementioning
confidence: 99%
“…Previous research on CBAs has suggested that districts with stronger unions and more restrictive contracts have greater expenditures (Eberts, 1983; Eberts & Stone, 1984; Marianno et al, 2021; Strunk, 2011), stemming in part from higher teacher salaries and benefits (Brunner & Squires, 2013; Hoxby, 1996; Winters, 2011). Earlier work has also shown that restrictive CBAs have either null or adverse effects on student outcomes (Marianno & Strunk, 2018; Moe, 2009; Strunk, 2011; Strunk & McEachin, 2011; see also Cowen & Strunk, 2015, for a more complete review of this literature).…”
Section: Teachers’ Collective Bargaining Agreements and Statewide Reformmentioning
confidence: 99%